Majorana oscillations modulated by Fano interference and degree of nonlocality in a topological superconducting-nanowire-quantum-dot system - Ricco, L. S. [UNESP]; Campo, V. L.; Shelykh, I. A.; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2018)
We explore theoretically the influence of Fano interference in the so-called Majorana oscillations in a T-shaped hybrid setup formed by a quantum dot (QD) placed between conducting leads and side coupled to a topological superconducting nanowire (TSNW) hosting zero-energy Majorana bound states (MBSs) at the ends. Differential conductance as a function of the external magnetic field reveals oscillatory behavior. Both the shape and amplitude of the oscillations depend on the bias voltage, degree of MBSs nonlocality, and Fano parameter of the system determining the regime of interference. When the latter is such that direct lead-lead path dominates over lead-QD-lead path and the bias is tuned in resonance with QD zero energy, pronounced fractional Fano-like resonances are observed around zero bias for highly nonlocal geometries. Further, the conductance profiles as a function of both bias-voltage and QD energy level display bowtie and diamond shapes, in qualitative agreement with both previous theoretical and experimental works. These findings ensure that our proposal can be used to estimate the degree of MBS nonlocality, thus allowing us to investigate their topological properties.